Antioxidant Potential of Ethanol Extract from Mango Parasite (Dendrophthoe petandra) to Maintain Crude Palm Oil (CPO) Quality - Ninik Triayu Susparini; Rohmatulloh; Boima Situmeang; Isna Lailatusholihah; Siti Rohmiyati (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
The present study aimed to determine the effectiveness of adding natural antioxidants from ethanolic extract of mango parasite (Dendrophthoe petandra) to oxidation stability of crude palm oil (CPO) during storage. The parameters tested were levels of free fatty acid (FFA), acid values, and deterioration of bleachability index (DOBI). The antioxidant activity of D. petandra extract obtained was IC50 of 6.369 ppm. Concentrations of D. petandra extract range from 200 to 1000 ppm. Based on the results, the ethanolic extract of D. petandra was able to reduce the FFA and acid value and increase the DOBI compared to the negative control. The lowest FFA levels and acid numbers were obtained from samples with addition of 1000 ppm natural antioxidants with FFA of 4.2% and acid value of 7.4 mg KOH/g, while the DOBI value increased to 1.300.